Relationships of beverage consumption and actigraphy-assessed sleep parameters among urban-dwelling youth from Mexico. Issue 7 (30th July 2022) - Jansen, Erica C; Corcoran, Kathleen; Perng, Wei; Dunietz, Galit L; Cantoral, Alejandra; Zhou, Ling; Téllez-Rojo, Martha M; Peterson, Karen E
Abstract: Objective: To examine whether usual beverage intake was associated with sleep timing, duration and fragmentation among adolescents. Design: Usual beverage intake was assessed with a FFQ. Outcomes included sleep duration, midpoint (median of bed and wake times) and fragmentation, assessed with 7-d actigraphy. Sex-stratified linear regression was conducted with sleep characteristics as separate outcomes and quantiles of energy-adjusted beverage intake as exposures, accounting for age, maternal education, physical activity and smoking. Setting: Mexico City. Participants: 528 adolescents residing in Mexico City enrolled in a longitudinal cohort. Results: The mean age (sd ) was 14·4 (2·1) years; 48 % were male. Among males, milk and water consumption were associated with longer weekday sleep duration (25 (95 % CI 1, 48) and 26 (95 % CI 4, 47) more minutes, in the 4th compared to the 1st quartile); and higher 100 % fruit juice consumption was related to earlier weekday sleep timing (−22 (95 % CI −28, 1) minutes in the 1st compared to the last quantile; P = 0·03). Among females, soda was associated with higher sleep fragmentation (1·6 (95 % CI 0·4, 2·8) % in the 4th compared to the 1st), and coffee/tea consumption was related to shorter weekend sleep duration (−23 (95 % CI −44, 2) minutes in the 4th compared to the 1st). Conclusions: Among females, adverse associations with sleep were observed for caffeinated drinks, while males with higher consumption of healthier beverage options (water, milk and 100 % juice) had evidence of longer and earlier-timed sleep. Potential mechanisms involving melatonin and tryptophan should be further investigated.